Assessing the sustainability gaps of food sharing platforms: a mixed-method approach - Tian, Shuang (2025)
Food waste and food poverty are two interlinked global crises with significant environmental, economic, and social implications. According to the Food and Agriculture Organization (FAO), nearly one-third of all food produced worldwide for human consumption is lost or wasted each year, contributing to vast amounts of greenhouse gas emissions and the depletion of critical resources such as water, land, and energy (FAO, 2017). At the same time, around 805 million people suffer from hunger and malnutrition worldwide, highlighting the moral urgency of addressing both food waste and its contributions to food insecurity (Sharma et al., 2016). This dual challenge underscores the need for innovative and sustainable solutions that not only reduce food waste but also tackle the widespread issue of food poverty.